2016
DOI: 10.1051/matecconf/20179001067
|View full text |Cite
|
Sign up to set email alerts
|

Steady flow and dynamic analyses comparison of an air intake breathing capacity

Abstract: Abstract. Analysis of intake breathing capacity is important in order to determine the performance output for any respective engine. Flow coefficient and discharge coefficient are the common parameters used to define the breathing capability and different analysis have been applied by researchers to determine these parameters which include experiments and Computational Fluid Dynamics (CFD) analyses. This study aims to investigate the difference in breathing parameters obtained from steady flow simulation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nur Adila Mohamad Shafie et al [6] showed that the minimum and maximum deviation as small as 1.6% and 5.1% respectively were obtained when they compared the results obtained by port flow simulation and those obtained from engine flow bench test(experimental test) which shows that port flow simulation can accurately predict the breathing parameter of engine.…”
Section: Flow In Cylindermentioning
confidence: 99%
See 1 more Smart Citation
“…Nur Adila Mohamad Shafie et al [6] showed that the minimum and maximum deviation as small as 1.6% and 5.1% respectively were obtained when they compared the results obtained by port flow simulation and those obtained from engine flow bench test(experimental test) which shows that port flow simulation can accurately predict the breathing parameter of engine.…”
Section: Flow In Cylindermentioning
confidence: 99%
“…Deviation in results obtained from Port flow simulation and engine flow bench (experimental test)[6] …”
mentioning
confidence: 99%